MODEL PEMBELAJARAN CTL (CONTEXTUAL TEACHING AND LEARNING) - Hasibuan, M. Idrus (IAIN PADANGSIDIMPUAN, 2014)
Learning in schoolsÂ not only focused on providing provisioning capabilities are theoretical knowledge, but also how to keep learning experience of the students is always associated with the actual problems that occur in the environment. Contextual learning (contextual teaching and learning) is a concept that can help teachers learn to associate the content to be studied with real-world situations students and encourage students to make connections between the knowledge possessed by its application in their lives as members of families and communities. Contextual learning focused onhow students understand the meaning of what they learned, what the benefits are, what state they are in, how to achieve it, and how they demonstrate what they have learned.